1999
DOI: 10.1021/bi991856n
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Binding of Small Molecule Isoprenoids to rhoGDP Dissociation Inhibitor (rhoGDI)

Abstract: The activities of small G-proteins are in part regulated by their interactions with GDI proteins. This binding is thought to be dependent on the C-terminal isoprenoid modification (geranylgeranyl or farnesyl) of these proteins. G-proteins are generally isoprenylated/methylated at their C-terminal cysteine residues. A quantitative fluorescence assay is reported here to evaluate the specificity of binding of rhoGDI. A rhodamine-labeled geranylgeranylated/methylated cysteine derivative is used to measure its bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 41 publications
7
42
0
Order By: Relevance
“…The weak binding observed in the absence of the methyl group is likely caused by the charge repulsion effect of the carboxylic acid group and the decreased hydrophobicity of farnesylated C185. Our results are in accordance with the previous findings showing that carboxymethylation of prenylated Rho peptide and catalytic subunits of PDE6 significantly increases their affinity for RhoGDI and PDEδ, respectively (33,36). Carboxymethylation is the only step in the posttranslational modification of the CaaX motif that is potentially reversible (37).…”
Section: Discussionsupporting
confidence: 93%
“…The weak binding observed in the absence of the methyl group is likely caused by the charge repulsion effect of the carboxylic acid group and the decreased hydrophobicity of farnesylated C185. Our results are in accordance with the previous findings showing that carboxymethylation of prenylated Rho peptide and catalytic subunits of PDE6 significantly increases their affinity for RhoGDI and PDEδ, respectively (33,36). Carboxymethylation is the only step in the posttranslational modification of the CaaX motif that is potentially reversible (37).…”
Section: Discussionsupporting
confidence: 93%
“…3). Moreover, it was shown that the binding affinity of RhoGDI-1 for the farnesylated and geranylgeranylated moiety is not really important (42).…”
Section: Discussionmentioning
confidence: 99%
“…4B). Calculations (see "Experimental Procedures") of the dissociation constants (K d ) revealed that half-maximal binding of PDE␦ to farnesyl is at 0.70 Ϯ 0.27 M, whereas that of PDE␦ to geranylgeranyl is at 19.06 Ϯ 2.41 M. The binding constant of farnesyl to PDE␦ is higher than that of another prenyl-binding protein, RhoGDI (K d ϭ 4.8 M), whereas geranylgeranyl has approximately 10 times less affinity for PDE␦ compared with RhoGDI (K d ϭ 1.6 M) (26). DISCUSSION We show that PDE␦ can interact with both farnesyl (C15) and geranylgeranyl (C20) side chains in the absence of polypeptides.…”
Section: Figmentioning
confidence: 95%